Experimental Bioactive Glass-Containing Composites and Commercial Restorative Materials: Anti-Demineralizing Protection of Dentin - Matej Par; Andrea Gubler; Thomas Attin; Zrinka Tarle; Andro Tarle; Tobias T. Tauböck (Biomedicines, 2021)
The purpose of this in vitro study was to investigate whether different types of experimental and commercial restorative dental materials can protect dentin against acid-induced softening. Experimental composites were prepared with a photocurable mixture of methacrylates and two types of bioactive glass (45S5 and a customized low-Na F-containing formulation). Human dentin samples were prepared from mid-coronal tooth slices and immersed in lactic acid solution (pH = 4.0) at 5 mm from set specimens of restorative material. After 4, 8, 12, 16, 20, 24, 28, and 32 days, surface microhardness of dentin samples and pH of the immersion solution were measured, followed by replenishing of the immersion medium. Microstructural analysis was performed using scanning electron microscopy. The protective effect of restorative materials was determined as dentin microhardness remaining statistically similar to initial values for a certain number of acid additions. Scanning electron microscopy showed a gradual widening of dentinal tubules and proved less discriminatory than microhardness measurements. To produce a protective effect on dentin, 20 wt% of low-Na F-containing bioactive glass was needed, whereas 10 wt% of bioactive glass 45S5 was sufficient to protect dentin against acid-induced demineralization. The anti-demineralizing protective effect of experimental and commercial restoratives on dentin was of shorter duration than measured for enamel in a previous study using the same experimental approach.